The Knowledge Utilization Process in Management and Organization - Duncan, W. Jack (Academy of Management Journal, 1972)
This article deals with the knowledge utilization process in management and organization and relates the concepts of knowledge flow to management education and development. Primary attention is given to the processes through which the knowledge development, application, and ultimate consumption subsystems are linked to one another within the entire knowledge flow system of administrative science.